Pengaruh Harga, Promosi, Suasana Toko dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Toko Kue Dapur Daya Tanjungbalai - Aprilia Indah Saputri Rambe; Tri Inda Fadhila Rahma; Wahyu Syarvina (Jurnal Manajemen Riset Inovasi, 2024)
This research aims to test the analysis of the influence of price, promotion, shop atmosphere, and service quality on purchasing decisions at the cake shop, Dapur Daya Tanjungbalai, both partially and simultaneously. This research aims to see whether there is an influence of price, promotion, shop atmosphere and service quality variables on purchasing decisions at the Dapur Daya cake shop. This research uses the Likert scale method. The subjects used in this research were 100 Power Kitchen consumers and were taken using accidental sampling and using the Lemeshow formula. In this research, data analysis uses validity tests, reliability tests, classical assumption tests, partial and simultaneous tests. Data analysis techniques using the IBM SPSS statistics 25 program. The results of this research show that overall each partial test states that there is a significant and positive effect between the variables. Based on the results of testing the coefficient of determination, the Adjusted R Square value was obtained, namely 0.984 or 98.4%. This means that the influence of the independent variables, namely price, promotion, shop atmosphere and service quality on the dependent variable, namely buyer decisions, is 98.4%. Meanwhile, 1.6% is influenced by other factors not included in the regression model.